Exam cheating and academic integrity breaches during the COVID-19 pandemic: An analysis of internet search activity in Spain. Issue 10 (October 2021) - Comas-Forgas, Rubén; Lancaster, Thomas; Calvo-Sastre, Aina; Sureda-Negre, Jaume
Abstract: Academic institutions worldwide have had to adapt their methods of teaching and assessment due to COVID-19. In many Spanish universities exams moved online, affording students with opportunities to breach academic integrity that were not previously available to them. This paper uses the emerging research method of search engine data analysis to investigate the extent of requests for exam cheating information in Spain in the time period surrounding adjustments for the pandemic. The Internet data analytics technique is one that the paper proposes should be used more widely as an academic integrity research method. For this study, search engine activity data on exam cheating in Spain was collected and analysed for the five-year period between 2016 and 2020 inclusive. The data suggests that students are searching for information about ways to cheat in exams, including how to create cheat sheets. Most strikingly, the results show a significant increase in requests for information on cheating on online exams during the COVID-19 timeframe and the Spanish lockdown period. Based on the findings, academic institutions in other regions should be wary about the opportunities that their students have to commit exam fraud. Abstract : Assessment; Exam cheating; Academic integrity; Spain; COVID-19.